WALLABY pilot survey: Public release of H i data for almost 600 galaxies from phase 1 of ASKAP pilot observations. (15th November 2022) - Westmeier, T.; Deg, N.; Spekkens, K.; Reynolds, T. N.; Shen, A. X.; Gaudet, S.; Goliath, S.; Huynh, M. T.; Venkataraman, P.; Lin, X.; O'Beirne, T.; Catinella, B.; et al.
Abstract: We present WALLABY pilot data release 1, the first public release of H i pilot survey data from the Wide-field ASKAP L-band Legacy All-sky Blind Survey (WALLABY) on the Australian Square Kilometre Array Pathfinder. Phase 1 of the WALLABY pilot survey targeted three $60\, deg^{2}$ regions on the sky in the direction of the Hydra and Norma galaxy clusters and the NGC 4636 galaxy group, covering the redshift range of $z \lesssim 0.08$ . The source catalogue, images and spectra of nearly 600 extragalactic H i detections and kinematic models for 109 spatially resolved galaxies are available. As the pilot survey targeted regions containing nearby group and cluster environments, the median redshift of the sample of $z ≈ 0.014$ is relatively low compared to the full WALLABY survey. The median galaxy H i mass is $2.3 × 10^{9}\, {\rm M}_{{\odot}}$ . The target noise level of $1.6\, mJy$ per 30 ′′ beam and $18.5\, kHz$ channel translates into a $5 σ$ H i mass sensitivity for point sources of about $5.2 × 10^{8} \, (D_{\rm L} / \mathrm{100\, Mpc})^{2} \, {\rm M}_{{\odot}}$ across 50 spectral channels ( ${≈} 200\, \mathrm{km \, s}^{-1}$ ) and a $5 σ$ H i column density sensitivity of about $8.6 × 10^{19} \, (1 + z)^{4}\, cm^{-2}$ across 5 channels ( ${≈} 20\, \mathrm{km \, s}^{-1}$ ) for emission filling the 30 ′′ beam. As expected for a pilot survey, several technical issues and artefacts are still affecting the data quality. Most notably, there are systematic flux errors of up to several 10% caused by uncertainties about the exact size and shape of each of the primary beams as well as the presence of sidelobes due to the finite deconvolution threshold. In addition, artefacts such as residual continuum emission and bandpass ripples have affected some of the data. The pilot survey has been highly successful in uncovering such technical problems, most of which are expected to be addressed and rectified before the start of the full WALLABY survey.